Source Municipal Management In Russia: The National Base Of The President And System Digitalization - Kalinichenko, Lyudmila A. (2021)
The purpose of the study is the diagnosis of practice and the introduction of new legal norms and digital technologies of municipal administration; life quality improvement and sustainable socio-economic development provision in all municipalities of vast Russia. The article analyzes the necessary changes in the Constitution of the Russian Federation (1993), which should ensure life quality increase and accelerated socio-economic development of municipalities. These include: the changes in the powers and functions of local governments; strengthening the responsibility of local administrations for social performance results. A search is underway for the optimal coordination of the functions and powers of federal, regional and municipal governments on a new constitutional basis. The scientific basis of municipal administration is being developed - the theory of municipal service as the managerial core of local self-government is proposed. The scientific methodology of the state and municipal services is correlated. New parameters of social responsibility of local government officials are defined. The possibilities of digital technologies are being studied to increase the effectiveness of municipal governance. The article proposes to conduct systemic digitalization of state and municipal government actively. New digital technologies are considered as a necessary scientific and informational basis to increase the effectiveness of local management. In the article, each of the proposed trends for municipal governance improvement is considered from the perspective of the possible interaction problem study between the authorities and citizens; the conflicts between authorities at various levels. They studied the danger of the destructive consequences of existing performance indicators, local management methods and technique conservation. They presented the perspectives of further research and officials and local administration efficiency and responsibility increase.